Perencanaan Perkerasan Kaku (Rigid Pavement) Jalan Untuk Lalu Lintas Berat Berdasarkan Manual Desain Perkerasan Bina Marga 2017 pada Ruas Jalan Tempino – Muara Bulian - Sheila Elysia Tiffany; Fakhrul Rozi Yamali; Ari Setiawan (Jurnal Talenta Sipil, 2026)
The design of rigid pavement thickness on the Tempino-Muara Bulian road section, specifically on segment STA 00+000 to STA 02+200. This road section has experienced significant damage due to the increased traffic volume of heavy vehicles, especially coal transportation. An analysis was conducted to determine the optimal rigid pavement thickness to withstand the increased load and compare it with the existing conditions. Using the AASHTO 1993 method, the required concrete slab thickness was calculated to be 28.016 cm. However, the 2017 Pavement Design Manual recommends a slightly thicker slab of 29.3 cm. Meanwhile, the existing condition of 30 cm indicates that the current pavement has been designed considering factors such as future traffic growth or to accommodate potential overload. This study demonstrates the importance of accurate pavement design to ensure long-term road serviceability under heavy traffic conditions.